Analgesia in labour and delivery. Issue 6 (June 2021) - Chu, Andy; Ma, Samson; Datta, Shreelata
Abstract: Pain is defined as "an unpleasant sensory or emotional experience associated with actual or potential tissue injury". Labour pain is encountered during contractions in labour, and patient satisfaction correlates closely to how well it is managed. Doctors commonly encounter acute pain in clinical practice which can be treated simply by applying some basic rules. However, pain due to labour requires specific management which falls outside the basic principles of acute pain management and it is important for practitioners who look after these patients to understand what can be offered. This review considers the basic principles of each of these techniques using some common clinical scenarios. The type of analgesia given will determine where labour takes place and this will be reflected in each case. Specifically, the World Health Organisation (WHO) analgesia ladder is not applicable in these patients because the periodic nature and the intensity of labour pain renders this model obsolete, although is applicable after delivery or after a caesarean section (CS) under general anaesthetic.